Palaeogeographic implications of differential inclination shallowing in permo-carboniferous sediments from the donets basin, Ukraine - Iosifidi, A; Niocaill, C; Khramov, A; Dekkers, M; Popov, V (Elsevier, 2010)
We present new palaeomagnetic data from Upper Carboniferous and Lower Permian grey and red sediments from the Donets Basin, Ukraine, part of the Palaeozoic East European Platform. Detailed demagnetization of these units reveals two ancient components of magnetization: component "B", which is carried by magnetite and pigmentary haematite, and a high unblocking temperature component "C", present only in the red beds, carried by detrital haematite. The "B" and "C" components both pass fold tests indicating a primary or a near primary-origin for magnetizations. The "C" component, however, yields palaeolatiudes that are consistently lower (by up to ~12° of latitude or ~ 1330 km) than those derived from the "B" component, and we argue that this is due to significant inclination-shallowing of the "C" component. A comparison with European reference palaeomagnetic data reveals that the reference data also span a large spread of palaeolatitudes for this time, and we argue that unrecognized shallowing may have crept into the reference data when based on sedimentary units. A more rigorous approach to selecting reference palaeomagnetic data may well be key to resolving palaeogeographic controversies at this time.